The price stability oriented monetary policy of the European Central Bank; Polityka Europejskiego Banku Centralnego w konteksćie stabilizacji cen - Wojciech Gasinśki; Anna Misztal (Comparative Economic Research. Central and Eastern Europe, 2010)
The aim of this paper is to present the price stability oriented monetary policy of the European Central Bank. The European Central Bank began activities in 1998 and the primary objective of the European System of Central Banks is to maintain price stability and the ESCB should also support the general economic policies in the Community. Monetary policy is a special tool that national governments and central banks uses to influence on its economy, especially to control the supply of money and to influence on the level of economic indicators. This paper investigates the assumed objective of the European System of Central Banks which is to maintain price stability. What is more, we would like to present the monetary policy strategy of the European Central Bank and analysis of the Harmonized Index of Consumer Prices. – – Celem niniejszego artykułu jest przedstawienie polityki pieniezṅej EBC w konteksćie stabilizacji cen. EBC rozpoczał swoja działalnosćẃ roku 1998 i od tego czasu wraz z Europejskim Systemem Bankoẃ Centralnych odgrywa istotna role w prowadzeniu polityki pieniezṅej Unii Europejskiej. Polityka ta jest specjalnym narzedziem stosowana przez bank centralny oraz rzady narodowe w celu oddziaływania na gospodarke. Jednym z działanj́est oczywisćie wpływ na podazṗieniadza i innych istotnych wskazńikoẃ. W niniejszym artykule autorzy staraja sie dokonacánalizy polityki pieniezṅej prowadzonej przez EBC ze szczegoĺnym uwzglednieniem HICP.
Keywords: 330